2019
DOI: 10.1371/journal.pcbi.1006633
|View full text |Cite
|
Sign up to set email alerts
|

Deep image reconstruction from human brain activity

Abstract: The mental contents of perception and imagery are thought to be encoded in hierarchical representations in the brain, but previous attempts to visualize perceptual contents have failed to capitalize on multiple levels of the hierarchy, leaving it challenging to reconstruct internal imagery. Recent work showed that visual cortical activity measured by functional magnetic resonance imaging (fMRI) can be decoded (translated) into the hierarchical features of a pre-trained deep neural network (DNN) for the same in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
201
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(206 citation statements)
references
References 27 publications
5
201
0
Order By: Relevance
“…Second, visual word features were derived directly from the structure of the EEG data and used for the purpose of word image reconstruction. Previous work has reconstructed single characters such as letters from fMRI patterns in visual cortex (Schoenmakers et al, 2013;Shen et al, 2019;Thirion et al, 2006) or visualized their representation through psychophysical methods (Gosselin & Schyns, 2003)-see also complementary work (Pasley et al, 2012) targeting ECoG-based speech reconstruction. In contrast, the current results demonstrate, for the first time to our knowledge, the ability to reconstruct the visual appearance of whole words from neural recordings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, visual word features were derived directly from the structure of the EEG data and used for the purpose of word image reconstruction. Previous work has reconstructed single characters such as letters from fMRI patterns in visual cortex (Schoenmakers et al, 2013;Shen et al, 2019;Thirion et al, 2006) or visualized their representation through psychophysical methods (Gosselin & Schyns, 2003)-see also complementary work (Pasley et al, 2012) targeting ECoG-based speech reconstruction. In contrast, the current results demonstrate, for the first time to our knowledge, the ability to reconstruct the visual appearance of whole words from neural recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Relevantly here, neural-based image reconstruction (Chang & Tsao, 2017;Naselaris, Prenger, Kay, Oliver, & Gallant, 2009;Nestor, Plaut, & Behrmann, 2016;Nishimoto et al, 2011;Shen, Horikawa, Majima, & Kamitani, 2019) aims to reveal the content of fine-grained visual representations by retrieving the appearance of visual objects from neural activity prompted by their processing. For instance, several fMRI studies have addressed the challenge of reconstructing the appearance of single letters from fMRI patterns associated with their reading (Miyawaki et al, 2008;Schoenmakers, Barth, Heskes, & van Gerven, 2013;Thirion et al, 2006).…”
mentioning
confidence: 99%
“…The fMRI data made it possible to decode DNN feature values from the brain activity patterns, and the estimated decodability was highly consistent across subjects. Thus, the present dataset could provide an opportunity to utilized for various purposes, including the feature selection in neural encoding and decoding analyses 4,8,10 and further applications by combining the decoded features with deep neural network technology 6,9 .…”
Section: Technical Validationmentioning
confidence: 99%
“…On the basis of the hierarchical representational similarity between the brain and DNNs, our recent study demonstrated that human brain activity measured by functional magnetic resonance imaging (fMRI) can be decoded (translated) into DNN feature values 6 . Combining those decoded DNN features and techniques developed with DNNs, recent work has started to develop new technologies to read out richer contents in the brain as demonstrated in the generic decoding of seen, imagined, and dreamed objects 6,7 and in the reconstruction of seen and imagined images 9 . As exemplified by these studies, decoding of DNN features from brain activity patterns can then provide opportunities to develop new technologies for further applications in brain machine interfacing.…”
Section: Background and Summarymentioning
confidence: 99%
“…In [15] authors presented an encoding model by which, starting by Convolutional Neural Network (CNN) layer activations and using ridge regression with linear kernel, they predict BOLD fMRI response, employing two different databases ([11] and [16]). In [17] the authors presented a novel image reconstruction method, in which the pixel values of an image are optimised to make its CNN features similar to those decoded from human brain activity at multiple layers. A further example of encoding came from [18], in which the prediction of brain response is done multi-subject and using Bayesian incremental learning.Whereas encoding models have greatly benefited from the inclusion of DNN-derived features in the modeling pipeline, decoding models have not yet exploited the full potential offered by them.…”
mentioning
confidence: 99%